Kolaborasi Antar-Aktor dalam Implementasi Kebijakan Ripparprov Banten di Kawasan Ekonomi Khusus Tanjung Lesung - Mohammad Arief Hidayatullah; Damanhuri Damanhuri; Aryanti Dwi Untari (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
This study examines how four key actors—the Banten Provincial Tourism Office, the Tanjung Lesung Special Economic Zone (SEZ) Administrator, the zone developer and manager PT Banten West Java (BUPP), and the local community represented by a tourism awareness group (Pokdarwis) and local craftspeople—collaborate in supporting the implementation of the Banten Tourism Development Master Plan (Ripparprov) 2018–2025 in Tanjung Lesung SEZ. Using a qualitative descriptive approach and the collaborative governance framework of Kurhayadi and Kushendar (2023), which identifies five critical factors (transparency and participation, communication and coordination, strong leadership, capacity and resources, and evaluation and monitoring), data were collected through semi-structured interviews with eight purposively selected informants, observation, and documentation review. The findings indicate that inter-actor collaboration in Tanjung Lesung SEZ remains partial, bilateral, and situational rather than integrated. Each actor interacts with others according to its own mandate, while no permanent, institutionalized forum brings all four actors together to plan, evaluate, and solve problems jointly. This absence weakens transparency toward the community, produces top-down rather than reciprocal communication, leaves facilitative leadership undeveloped, perpetuates capacity gaps between the private developer and local communities, and excludes community perspectives from evaluation processes. The study concludes that effective implementation of Ripparprov requires structural reform of collaborative mechanisms, particularly the establishment of a regular multi-stakeholder forum, rather than merely expanding individual program budgets.Keywords: collaborative governance; multi-actor collaboration; policy implementation; special economic zone; tourism